Degenerative changes in the ankle in former elite high jumpers - Schmitt, H.; Lemke, J. M.; Dario, R. C.; Parsch, D. (Clinical Journal of Sport Medicine, 2003)
Objective: The object of this study was to find what degenerative changes are present in the ankle (talotibiofibular) joints in former elite high jumpers at least 10 years after their retirement from competition, whether there are differences between takeoff and swinging leg, and whether correlations between any particular training history parameters, former injuries, and the degenerative changes can be recognized. Design: A cross-sectional case control study with matched controls for radiological outcomes. Setting: The Orthopedic Department at the University of Heidelberg, Germany. Participants: The subjects were 40 male high jumpers (required personal best at least 2.18m), featured in the lists of top athletes kept by the German Athletics Association (DLV) from 1972 to 1986. All radiological findings were compared with X-rays of male age, and BMI-matched controls. Main Outcome Measurements: All underwent clinical and radiological examinations. In addition to eliciting data on the training history with the aid of a questionnaire, we assessed symptoms affecting the ankle by means of the Freiburg Ankle Score and the Kitaoka Score and scored the radiological findings according to Bargon and Scranton and MacDermott. Results: Differences between takeoff and swinging leg were small (Freiburg takeoff leg 93/swinging leg 95, Kitaoka takeoff 89/swinging leg 93 points on a 100 points scale) in both clinical scores, but statistically significant (p < 0.005). The more jumps were performed during the active phase, the worse the radiological scores (rs = 0.4, p = 0.01). Radiological differences between takeoff and swinging leg were not found. Comparison with controls revealed no radiological differences between athletes and age- and BMI-matched men (all p-values >0.40). It was found that one takeoff and one swinging leg ankle was affected by grade 2 arthritis (Bargon). Scranton grade 3 was found in four takeoff and in three swinging legs. No further correlations with training history data were found. Athletes who reported injuries in the past tended to have poorer radiological scores, although statistically not significant. None of the athletes had an instable ankle. Conclusions: The talotibiofibular joints in former high jumpers showed only slight signs of wear and tear with no clinically relevant side-related differences; severe arthrosis with narrowing of the joint space was rare. The risk of arthrosis connected with high-jumping seems not to be elevated.